Cone-Beam Computed Tomographic Assessment of Anatomical Variations of the Interforaminal Region in a Selected Iranian Population - Valizadeh, Solmaz; Alesheikh, Hessam; Iranparvar Alamdari, Mina (Journal of Dental School, 2021)
Objectives This study assessed the anatomical variations of the mental foramen (MF) and presence and length of the anterior loop and the incisive canal in a selected Iranian population using cone-beam computed tomography (CBCT). Methods This descriptive, cross-sectional study evaluated CBCT scans of 256 patients (123 males, 133 females) over 18 years of age. The CBCT multiplanar reformatted panoramic images (10-mm thickness) were used to assess the anatomical position of the MF and presence/absence and length of the anterior loop. The cross-sectional images were used to assess the presence/absence and length of the incisive canal. The anatomical variations were compared in the right and left sides and between males and females using dependent and independent t-test. SPSS version 21was used for statistical analysis. Results The most common position of MF was adjacent to the apex of the second premolar, noted in 41.4% of the patients. The second common position of MF was between the apices of the first and second premolars (30.1% of the patients). The anterior loop was present in 44.3% of the patients. The mean length of the anterior loop and the incisive canal was 2.64 mm and 7.15 mm, respectively. No significant difference was noted between males and females or right and left sides in any variable (P>0.05). Conclusion Anatomical variations of the anaterior mandible indicate the significance of 3D imaging to prevent nerve traumatization by proper treatment planning.